1998
DOI: 10.1016/s1074-7613(00)80630-5
|View full text |Cite
|
Sign up to set email alerts
|

CD8 Expression Allows T Cell Signaling by Monomeric Peptide-MHC Complexes

Abstract: Physiologically, TCR signaling is unlikely to result from the cross-linking of TCR-CD3 complexes, given the low density of specific peptide-MHC complexes on antigen-presenting cells. We therefore have tested directly an alternative model for antigen recognition. We show that monomers of soluble peptide-MHC trigger Ca2+ responses in CD8alphabeta+ T cells. This response is not observed in CD8- T cells and when either the CD8:MHC or CD8:Lck interactions are prevented. This demonstrates that an intact CD8 corecept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
5
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 55 publications
7
112
5
1
Order By: Relevance
“…These studies on the molecular reorganization of cell surface receptors that accompanies the transition from naive to activated T cells complement earlier work, demonstrating the reorganization of cell surface molecules into a supramolecular activation complex, or immunological synapse, following exposure of T cells to APC (37)(38)(39)(40). It will be of interest to determine whether these findings that compare functional avidities between naive and activated peripheral T cells can be extended to explain the different functional avidities observed when T cells with identical TCRs develop in different thymic environments.…”
Section: Discussionsupporting
confidence: 75%
“…These studies on the molecular reorganization of cell surface receptors that accompanies the transition from naive to activated T cells complement earlier work, demonstrating the reorganization of cell surface molecules into a supramolecular activation complex, or immunological synapse, following exposure of T cells to APC (37)(38)(39)(40). It will be of interest to determine whether these findings that compare functional avidities between naive and activated peripheral T cells can be extended to explain the different functional avidities observed when T cells with identical TCRs develop in different thymic environments.…”
Section: Discussionsupporting
confidence: 75%
“…Doucey, D. F. Legler, N. Boucheron, J.-C. Cerottini, C. Bron, and I. F. Luescher, manuscript in preparation). It has been reported that CD8 ϩ T cells are activated by monomeric K d -peptide complexes, but in this study the cells were adhered and not in suspension (33).…”
Section: Discussionmentioning
confidence: 91%
“…T cell hybridomas were cultured in DMEM (Life Technologies, Gaithersburg, MD) supplemented with 5% (v/v) heat-inactivated FCS (HIFCS, Life Technologies), penicillin-streptomycin-neomycin (PSN, Life Technologies), and 2-ME. The T1.4.1 ␣␤ and T1.4.1 ␣Ј␤ (␣ tailless) and T1.4.1 ␣Љ␤ (CD8␣ lck binding site mutant) transfectants (33) were cultured in the presence of 2 mg/ml G418 (Life Technologies). T1.4.2 ␣␣ transfectants were cultured in the presence of 2 mM histidinol (Sigma), whereas T1.4.2 ␣␤ and T1.4.2 ␣␤Ј (␤ tailless) transfectants were cultured in DMEM containing 1.5% (v/v) HIFCS supplemented with 2 mM histidinol and 3 g/ml puromycin (Calbiochem, La Jolla, CA).…”
Section: Cell Culturementioning
confidence: 99%
“…Engagement of the MHC coreceptor CD8 has been proposed to play an important role in activation of CD8 T cells (12,21,34). In the current experiments, we had an opportunity to study the activation responses of CD8 ϩ 2C T cells (ϳ75-80% of lymph node T cells) vs a naturally occurring population of CD8 Ϫ T cells also found in the 2C transgenic mice (ϳ20 -25% of lymph node T cells) (Fig.…”
Section: Allogeneic Mhc-peptide Complexes Activate Cd8 T Cells As Olimentioning
confidence: 99%